2017
DOI: 10.1099/mic.0.000567
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis to self-generated AI-2 promotes biofilm formation in Escherichia coli

Abstract: Responses to the interspecies quorum-sensing signal autoinducer-2 (AI-2) regulate the patterns of gene expression that promote biofilm development. Escherichia coli also senses AI-2 as a chemoattractant, a response that requires the periplasmic AI-2-binding protein LsrB and the chemoreceptor Tsr. Here, we confirm, as previously observed, that under static conditions highly motile E. coli cells self-aggregate and form surface-adherent structures more readily than cells lacking LsrB and Tsr, or than ΔluxS cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 58 publications
2
59
2
Order By: Relevance
“…It allows bacteria to navigate in environmental gradients of various chemicals [ 25 27 ] in order to locate conditions that are beneficial for growth [ 28 ]. Chemotaxis to self-secreted signals can also mediate collective behaviors, such as the autoinducer-2 dependent autoaggregation and biofilm formation by E. coli [ 29 , 30 ]. The chemotactic signal transduction pathway of E. coli includes two high-abundance (or major) receptors, Tsr and Tar, as well as three low-abundance (or minor) receptors, Trg, Tap, and Aer.…”
Section: Introductionmentioning
confidence: 99%
“…It allows bacteria to navigate in environmental gradients of various chemicals [ 25 27 ] in order to locate conditions that are beneficial for growth [ 28 ]. Chemotaxis to self-secreted signals can also mediate collective behaviors, such as the autoinducer-2 dependent autoaggregation and biofilm formation by E. coli [ 29 , 30 ]. The chemotactic signal transduction pathway of E. coli includes two high-abundance (or major) receptors, Tsr and Tar, as well as three low-abundance (or minor) receptors, Trg, Tap, and Aer.…”
Section: Introductionmentioning
confidence: 99%
“…AI-2 is the only known QS molecule produced by the enteric bacterium Escherichia coli , and its production and uptake were shown to affect several E. coli phenotypes, including biofilm formation, motility, and virulence ( 21 , 22 ). Previous work showed that, during autoaggregation or biofilm formation by E. coli , AI-2 serves as a chemoattractant that recruits planktonic cells to growing cell aggregates ( 23 25 ). However, it remained unclear whether and how E. coli could use this AI-2-mediated autoaggregation in mixed microbial communities in which it represents only a minor fraction of the population.…”
Section: Introductionmentioning
confidence: 99%
“…The escape band is a general phenomenon not limited by specific chemoattractants or receptors, and it should be physiologically relevant, as it enhances the fitness of the population by avoiding being trapped by nonmetabolizable or weakly metabolizable attractants, such as AI-2 in the biofilm (32,33) and DHMA for commensal bacteria in the gut microbiota (34,35). Indeed, our model showed that the overall population growth starving E.coli growing E.coli rate increases as the system changes from the no-band-forming regime to the band-forming regime (SI Appendix, Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%